Early triassic temnospondyl skull fragments from southern South America (Paraná Basin, Brazil) - Dias da Silva, Sergio (2005)
Fragmentary eotriassic temnospondyl skull remains have been recovered from levels of the Sanga do Cabral Formation in the Paraná Basin. Despite the fragmentary nature of the material, several specimens can be identified and described herein. Some are tentatively attributed to rhytidosteids, based on the ornamentation of the dermal bones, and others are identified simply as Temnospondyli incertae sedis. The rhytidosteids seem to have dominated aquatic environments during the Early Triassic and some paleoecological implications are discussed. In the Upper Permian, medium-large rhinesuchid faunas inhabited the Paraná Basin and by the end of Paleozoic they become extinct. During the Lower Triassic, they were replaced, by a quite abundant fauna mainly represented by small rhytidosteids. The uppermost Permian strata in the Paraná Basin are represented by the Pirambóia Formation which was deposited under aeolian conditions. so the environmental conditions had changed from humid to arid. This could help to explain the ‘sudden’ disappearance of the rhinesuchids from this depocenter at the end of Permian. When more humid conditions returned to this basin during the Early Triassic, the rhytidosteids might had been the first group to arrive. However, an alternative explanation is that this abundance of rhytidosteids be a taphonomic artifact that only preserved animals from selected habitats.